2018
DOI: 10.3389/fmicb.2018.01909
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Pulse Rotations Buildup Pea Rhizosphere Pathogens in Cereal and Pulse Based Cropping Systems

Abstract: The association of plants and microbial communities is crucial for crop production, and host plants influence the composition of rhizosphere microbiomes. Pulse crops play an important role in the development of sustainable cropping systems, and producers in the Canadian prairies often increase the frequency of pulses in their cropping systems. In this study, we determined the shifts in the fungal community of pea (Pisum sativum L.) rhizosphere, as influenced by the frequency of pulses in rotation, using high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 74 publications
2
17
0
Order By: Relevance
“…Short-term (3–5 years, etc.) field experiments can help determine the temporary change of soil microbial community in relation to farming practices [ 34 , 37 , 38 ], while long-term (>10 years) field experiments may allow researchers to learn what would happen in the soil environment under different farming practices. Our results from the 18 years of soil treatments (tillage, crop residue management) demonstrated that cropping practices had a significant effect on soil physiochemical properties and the composition of soil microbiomes.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term (3–5 years, etc.) field experiments can help determine the temporary change of soil microbial community in relation to farming practices [ 34 , 37 , 38 ], while long-term (>10 years) field experiments may allow researchers to learn what would happen in the soil environment under different farming practices. Our results from the 18 years of soil treatments (tillage, crop residue management) demonstrated that cropping practices had a significant effect on soil physiochemical properties and the composition of soil microbiomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, other Olpidium species are virus-transmitting plant pathogens. Zoospores of Olpidium virulentus colonize roots of various plant species, and were demonstrated to accumulate in crop rotation with multiple pulses including pea (Niu et al, 2018).…”
Section: Can We Pinpoint Nematode-suppressive Bacterial or Fungal Taxmentioning
confidence: 99%
“…Although studies on H. oryzae are scarce, its role in promoting plant growth has been confirmed (45). Mortierella has been reported to be enriched in the fungal community associated with the pea rhizosphere (46), with its abundance being sensitive to root type (47) and climate change (48). In addition, Mortierella could enhance stress tolerance in host plants (49,50), including adaptability to low temperatures (51).…”
Section: Discussionmentioning
confidence: 99%